DAMPAK SOSIAL PERDA TENTANG PENGENDALIAN KEBAKARAN HUTAN DAN ATAU LAHAN TERHADAP MASYARAKAT SUMATERA SELATAN - Alva Beriansyah; Erik Darwawan; Mariatul Qibtiyah (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2022)
AbstractThis study analyzes the social impact of the South Sumatra regional regulation number 8 of 2016 regarding the control of forest and/or land fires on the people of South Sumatra. South Sumatra Province is a province that experienced very severe forest and/or land fires in 2015, covering an area of 736,587 hectares even though forests have many benefits for maintaining world climate stability. Forest and/or land fires that continue to occur every year bring tremendous losses, so the South Sumatra government issued a policy in the form of Regulation Number 8 of 2016 concerning Forest and/or Land Fire Control in order to minimize forest fire disasters in South Sumatra. This study uses a comparative qualitative research method. The data analysis technique uses Causal-Comparative Research (CCR) which investigates the causal relationship of a phenomenon. The results of the research in this report indicate that this regional regulation has resulted in social changes for the community in all aspects. Although the socialization of this regulation is still not comprehensive and does not touch community groups as its main target, the enactment of this regulation has resulted in very basic changes to farming community groups and planters in terms of land clearing techniques. The presence of a regional regulation that prohibits land clearing using burning techniques is not accompanied by alternative solutions for land clearing techniques without burning so that the community suffers losses from the existence of this regulation. With this regional regulation, it is hoped that the provincial government of South Sumatra will not only issue banning regulations without any alternative solutions that will have a negative impact on the people of South Sumatra.Keywords: Social Impact, Local Regulation, Fire, Forest/LandAbstrakPenelitian ini menganalisa dampak sosial peraturan daerah Sumatera Selatan nomor 8 tahun 2016 mengenai pengendalian kebakaran hutan dan atau lahan terhadap masyarakat Sumatera Selatan. Provinsi Sumatera Selatan adalah provinsi yang mengalami kebakaran hutan dan atau lahan yang sangat parah pada tahun 2015, yaitu seluas 736.587 Ha padahal hutan memiliki banyak manfaat untuk menjaga stabilitas iklim dunia. Kebakaran hutan dan atau lahan yang terus terjadi tiap tahunnya ini mendatangkan kerugian yang luar biasa sehingga pemerintah Sumatera Selatan mengeluarkan kebijakan berupa Peraturan Nomor 8 Tahun 2016 tentang Pengendalian Kebakaran Hutan dan atau Lahan guna meminimalisir bencana kebakaran hutan yang ada di Sumatera Selatan. Penelitian ini menggunakan metode penelitian kualitatif yang bertipe komparatif. Teknik analisa datanya menggunakan Causal-Comparative Research (CCR) yang menyelidiki hubungan sebab akibat dari sebuah fenomena. Hasil penelitian dalam laporan ini menunjukkan bahwa perda ini telah mengakibatkan perubahan sosial bagi masyarakat dalam segala aspek. Meskipun sosialisasi terhadap perda ini masih kurang menyeluruh dan tidak menyentuh kelompok masyarakat sebagai sasaran utamanya namun pemberlakuan perda ini telah mengakibatan perubahan yang sangat mendasar pada kelompok masyarakat pertani dan pekebun dalam hal teknik membuka lahan. Kehadiran perda yang melarang membuka lahan dengan teknik membakar tidak diiringi dengan alternatif solusi teknik membuka lahan tanpa pembakaran sehingga masyarakat mengalami dampak kerugian dari adanya perda ini. Dengan adanya perda ini, diharapkan pemerintah provinsi Sumatera Selatan tidak hanya mengeluarkan regulasi pelarangan tanpa ada solusi alternatif yang membawa dampak negatif bagi masyarakat Sumatera Selatan.Kata kunci: Dampak Sosial, Perda, Kebakaran, Hutan/Lahan